ANALISIS PUTUSAN HAKIM TERHADAP TINDAK PIDANA KORUPSI YANG DILAKUKAN PEJABAT DAERAH DENGAN MAKSUD MENGUNTUNGKAN DIRI SENDIRI ATAU ORANG LAIN - Gilang Sujaman; Syahrul Anwar; Suradi (PT. Saha Kreasi Indonesia, 2025)
One of the state's major issues is corruption, particularly when it affects public servants. The corruption case involving the chairman of the Banjar City Council and several council members is one that has garnered public attention. Article 3 Jo Article 18 of Law Number 31 of 1999 for the Eradication of Corruption is violated in this case. This journal will examine how the judge's ruling in this case represents attempts to uphold the law against collaborative corruption by municipal authorities. The purpose of this study is to provide more light on the social and legal ramifications of local corruption as well as the efficiency of the legal system in combating corruption.